2020
DOI: 10.1021/acsestengg.0c00081
|View full text |Cite
|
Sign up to set email alerts
|

Will Membranes Break Barriers on Volatile Fatty Acid Recovery from Anaerobic Digestion?

Abstract: The conversion of organic waste into value-added chemicals provides a sustainable pathway toward a circular economy, but anaerobic digestion (AD) as an established technology has faced great challenges primarily due to the low value of its primary productbiogas. Recent developments on arrested methanogenesis allow the AD process to be rewired to suppress methanogenesis and promote the production of higher valued volatile fatty acids (VFAs). However, the separation and recovery of VFAs from the mixed reactor c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(27 citation statements)
references
References 98 publications
0
27
0
Order By: Relevance
“…e study in [13] found that the first person who is different from the forward logistics network, especially the location of the recycling center, especially the distributor, needs to accept many and scattered logistics sources, and its location is characterized by "many to few" or even "many to one," and the traditional facility location model has been improved and perfected. e study in [14] summarized some basic characteristics of the reverse resource network system, including high complexity of network, complex diversity of targets, imbalance between supply and demand, and "from more to less" characteristics.…”
Section: Related Workmentioning
confidence: 99%
“…e study in [13] found that the first person who is different from the forward logistics network, especially the location of the recycling center, especially the distributor, needs to accept many and scattered logistics sources, and its location is characterized by "many to few" or even "many to one," and the traditional facility location model has been improved and perfected. e study in [14] summarized some basic characteristics of the reverse resource network system, including high complexity of network, complex diversity of targets, imbalance between supply and demand, and "from more to less" characteristics.…”
Section: Related Workmentioning
confidence: 99%
“…Purification and concentration of a product are critical to its value and the overall economics of the process. VFAs may be separated from a waste stream by using membrane technologies driven by either heat (e.g., membrane distillation) or electricity (e.g., electrodialysis) (Aktij et al, 2020; Zhu et al, 2020). The application of the produced VFAs that does not need separation, for example as a carbon source for biological nutrient removal, should also be explored.…”
Section: Resultsmentioning
confidence: 99%
“…The membrane contactor uses a hydrophobic porous membrane to separate the two aqueous phases on opposite sides of the membrane, avoiding mixing (Figure 2) [14,106]. The commonly used polymers in membrane contactors, selected based on their properties, such as mechanical stability, chemical resistance, and hydrophilic or hydrophobic characteristics, are polypropylene (PP), polyvinylidene fluoride (PVDF), and polytetrafluoroethylene (PTFE) [107].…”
Section: Membrane Contactormentioning
confidence: 99%
“…The term pervaporation represents the combination of the "permeation" and "evaporation" processes [105]. Pervaporation membranes can also be broadly categorized into two groups based on the target molecule to be recovered: hydrophilic pervaporation membranes ensure rapid water transport, allowing for effective dehydration, whereas organophilic pervaporation membranes provide better transport of organic compounds, making them suitable for VFA recovery [106]. The hydrophilic membrane is made of polyvinyl alcohol (PVA) [123] and sulfonated polybenzimidazole (SPBI) [124].…”
Section: Membrane Pervaporationmentioning
confidence: 99%